Programas de auditório: o tom como traço identitário - Stürmer, Adriana (2018)
The present thesis aims at investigating the role performed by the tone as a distinctive trace of different televisual products which belong to the same subgenre – the talk shows –, as well as its possible incidence in the shows identity characterization process within the same TV network. The adopted methodological path on examining one airing of each one of the talk shows selected for analysis, inspired by the hjelmslevian theoretical postulates and by propositions of the greimasian discursive semiotics, is an adaptation of the methodology which has been developed in the ambit of the research group „Comunicação Televisual‟ – ComTV(CNPq) –, of UFSM, to the objectives and object of study of this investigation. The corpus of research is composed by four talk shows belonging to the two Brazilian TV networks which more often air this subgenre in the country, „TV Globo‟ (12 shows) and „Sistema Brasileiro de Televisão‟ (SBT – 11 shows): Caldeirão do Huck and Domingão do Faustão (TV Globo); Programa Raul Gil and Programa Silvio Santos (SBT). The analyses were carried out, thus, considering: (1) the paratextual relations, which bear the operation method of the TV networks, a brief history of this subgenre on Brazilian television, an updated overview of the talk shows aired on programming schedules of the country‟s major TV networks – TV Globo, SBT, Record and Band –, as well as a characterization of the two networks which air the analyzed shows (TV Globo and SBT); (2) the intertextual relations of paradigmatic character, which characterize the talk shows concerning their configurations of genre, subgenre, format, and tone; (3) the intratextual relations, which indicate how the procedures of tonalization pass by the update of the other discursive/expressive devices; (4) the intertextual relations of syntagmatic character, which examine how these texts recover or appropriate other texts, focusing tonalization procedures used in these adaptations. Finally, this work presents a comparison, confronting obtained results in order to verify, concerning the configuring tones of each one of the airings, those which are common to all analyzed shows; those which are reiterated by the shows within the same network; as well as those that distinguish productions, amongst themselves, and those of each of the two networks.